Re-personalizing Recognition in a Highly Formalized Context: A Case Study on Novel Recognition Approaches for the Health Care Sector in the Netherlands (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
When It comes to recognition, the regulated health care professions are often cited as the context par excellence where rigorous formal standards should be maintained (“I should be certain the skills and competencies of the doctor performing surgery on me have been thoroughly checked”), and therefore heavily bureaucratized procedures for international recognition of professions within this sector are often regarded as an inevitable necessity in public discourse. However, gaining access to regulated health care professions is often perceived as an arduous process from the perspective of the international health care worker, especially when their learning experiences have predominantly taken place in a non-European/Western context. In the Netherlands, recognition in the context of the health care sector is multifaceted due to a variety of actors and authorities involved, and the formal process candidates must undergo is poorly understood by both the candidate and by many employers in the health care sector. In addition, the process of recognition takes place in a complex sociocultural setting, where candidates have to navigate numerous challenges, from strained financial resources, difficulties in finding adequate housing, language barriers, cultural differences in conducting work, and cases of outright discrimination. As a consequence, under-recognition, and under-employment are widespread among migrant health care professionals, impacting both the individual worker and society, as a shortage in workers is already putting pressure on the current health care system of the Netherlands. As a response, the municipality of The Hague initiated a pilot with a holistic and interpersonal approach to enhance the long-term employability of migrant health care professionals. An active network of migrant health care professionals with a large diversity in backgrounds was established (e.g., age, nationality, level of education, legal status), as well as a network of employers in the health care sector. The municipality organizes participative sessions for employers who are seeking solutions for their understaffed facilities, as well as informal activities for the healthcare workers, such as language cafés. Even as candidates await the results of the formal recognition of their professional qualifications, recognition at an employment level now takes place in a context-sensitive, interpersonal setting where employers and candidates engage in finding solutions to overcome barriers to sector-specific employment. The ENIC-NARIC of the Netherlands participates in the pilot, experimenting with a novel methodology for its credential evaluations. Candidates of the pilot are offered the opportunity to participate in a process to validate their previous informal learning experiences, with a focus on transferable skills (This trajectory is coordinated by a specialized organization for the Validation of Previous Learning). In addition, candidates receive an extensive credential evaluation of the ENIC-NARIC in an experimental format. This document contains a detailed description of the formal and non-formal learning that took place, with a focus on the acquired learning outcomes. When possible, the learning outcomes are connected to skills from the ESCO classification system. In this way, the focus is meant to shift away from a singular comparative statement towards a more descriptive format. This approach is meant to create a more substantive understanding of the learning that took place and guide potential conversations about the skills and competencies that were obtained by the learner. In this sense, the methodology allows for space to re-personalize the act of recognition within the highly formalized context of health care. This presentation will discuss the first outcomes and effects of the pilot, identify challenges, and lessons learned. Keywords: health care, VPL, highly formalized recognition